Plastic pre-compression and creep damage effects on the fracture toughness behaviour of Type 316H stainless steel - Mehmanparast, Ali; Davies, C. M.; Dean, David W.; Nikbin, Kamran (Elsevier, 2014)
The influence of inelastic damage in the form of plastic pre-strain and creep damage, on fracture toughness of Type 316H stainless steel has been examined. Creep damage has been introduced into the 8% pre-compressed material by interrupting creep crack growth tests. Comparisons have been made between the fracture toughness test results from the as-received, pre-compressed and creep damaged materials. Furthermore, the effects of creep crack discontinuities on the crack tip strain fields have been examined by digital image correlation measurements. Inelastic damage was found to reduce the fracture toughness of the material, with creep damage having more severe effects than pre-strain.
Keywords: Creep damage; Fracture toughness; Pre-straining; 316H stainless steel; Micro cracks; Crack discontinuity; DIC measurements